1985
DOI: 10.1148/radiology.157.2.4048441
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of calcified intracranial lesions.

Abstract: Fifty calcified intracranial lesions diagnosed with computed tomography (CT) were evaluated with magnetic resonance (MR) using a spin-echo sequence. MR images demonstrated 41 of 50 lesions seen as calcified on CT scans, among them 29 of 30 cerebral neoplasms and all ten arteriovenous malformations. The presence of calcification was suspected prospectively in about 60% of calcified lesions but was also suspected in 45% of uncalcified lesions (reviewed as control cases). No fine calcifications and only 25% of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
5

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(37 citation statements)
references
References 0 publications
4
26
0
5
Order By: Relevance
“…In fact, this is what we observed. Similar observations have been made in the MR imaging studies of children (14).…”
Section: Resultssupporting
confidence: 87%
“…In fact, this is what we observed. Similar observations have been made in the MR imaging studies of children (14).…”
Section: Resultssupporting
confidence: 87%
“…The above findings correlated with literature. 10,11,12 Ependymoma In this study there was one case of ependymoma (2%), which correlates with the reported literature. 13,14 According to Gregory B Nazar et al 14 ependymomas are the third most common paediatric brain tumour and two-third are infratentorial in location.…”
Section: Oligodendrogliomasupporting
confidence: 91%
“…Melanoma and neurofibromatosis can also be differentiated from Mn deposits from knowledge of the site and symmetry of the signals. The signal intensity of calcification can be shown as diminished, null effect, or increased in T1-weighted MRI [26][27][28][29][30][31][32] . Increased signal is only seen with low concentration of calcium, and the signal intensity progressively decreases as the calcium concentrations increase above 30-40% by weight 27) .…”
Section: Mn-induced High Signals Should Be Differentiated From High Smentioning
confidence: 99%